ARMED EXTORTION IN LIGHT OF THE PRINCIPLE OF CRIMINAL LEGALITY - RAMAZANI BABOLA Niclette, (IJRDO - Journal of Social Science and Humanities Research, 2025)
Furthermore, the DRC's military courts and tribunals fail to respect the principle of legality of offenses and penalties, in that they conflate the offense of armed robbery with that of armed extortion, which is not yet criminalized under Congolese criminal law.Extortion, however, is distinguished from theft by the fact that the thief, operating with violence or threats and taking advantage of the victim's helplessness, seizes the desired item himself.From the above, it is appropriate to summarize the issue with the following questions:- Why is armed extortion conflated with armed robbery?- How is armed extortion punished in Kisangani?The following answers are provided:- Armed extortion would be conflated with armed robbery due to the absence of specific criminal provisions.- In Kisangani, armed extortion is reportedly punished in the same way as armed robbery.This study was based on the observation that in several judgments of the Kisangani High Court and the Tshopo Court of Appeal, the perpetrators are convicted of armed robbery, whereas the facts reveal that the victims actually handed over the items rather than fraudulently removing them without their knowledge. This is completely illegal and unfair.After analyzing various judgments of the Tshopo Court of Appeal and the various judgments of the Kisangani High Court, it is clear that only armed extortion is actually punished in the same way as armed robbery by these courts. Furthermore, it appears that armed extortion is confused with armed robbery due to the absence of specific criminal provisions. This means that these results confirm our hypotheses.